Combined effects of bone morphogenetic protein 10 and crossveinless‐2 on cardiomyocyte differentiation in mouse adipocyte‐derived stem cells. Issue 3 (6th June 2017) - Jumabay, Medet; Zhumabai, Jiayinaguli; Mansurov, Nurlan; Niklason, Katharine C.; Guihard, Pierre J.; Cubberly, Mark R.; Fogelman, Alan M.; Iruela‐Arispe, Luisa; Yao, Yucheng; Saparov, Arman; Boström, Kristina I.
Abstract : Bone morphogenetic protein (BMP) 10, a cardiac‐restricted BMP family member, is essential in cardiomyogenesis, especially during trabeculation. Crossveinless‐2 (CV2, also known as BMP endothelial cell precursor derived regulator [BMPER]) is a BMP‐binding protein that modulates the activity of several BMPs. The objective of this study was to examine the combined effects of BMP10 and CV2 on cardiomyocyte differentiation using mouse dedifferentiated fat (mDFAT) cells, which spontaneously differentiate into cardiomyocyte‐like cells, as a model. Our results revealed that CV2 binds directly to BMP10, as determined by co‐immunoprecipitation, and inhibits BMP10 from initiating SMAD signaling, as determined by luciferase reporter gene assays. BMP10 treatment induced mDFAT cell proliferation, whereas CV2 modulated the BMP10‐induced proliferation. Differentiation of cardiomyocyte‐like cells proceeded in a reproducible fashion in mDFAT cells, starting with small round Nkx2.5‐positive progenitor cells that progressively formed myotubes of increasing length that assembled into beating colonies and stained strongly for Troponin I and sarcomeric alpha‐actinin. BMP10 enhanced proliferation of the small progenitor cells, thereby securing sufficient numbers to support formation of myotubes. CV2, on the other hand, enhanced formation and maturation of large myotubes and myotube‐colonies and was expressed by endothelial‐like cells in the mDFAT cultures. Thus BMP10 and CV2 have important roles in coordinating cardiomyogenesis in progenitor cells. Abstract : BMP10 and CV2 affect cardiomyogenesis in vitro.